Controlling for biases in primary valuation studies: A meta-analysis of international coral reef values - Sabah Abdullah; Randall S. Rosenberger (Fondazione Eni Enrico Mattei (FEEM), 2012)
This paper updates the existing meta-analysis in coral reef recreation taking into account the previous work of Brander et al. (2007) but considering some stated preference biases and/or effects. The present meta-analysis uses twice the number of observations as the previous one and sheds more light in understanding the influence of these common biases and/or effects found in valuations. The results show the common biases/effects in varied methodology types significantly influence the willingness to pay (WTP) estimates and in turn this has implications in welfare and benefit transfer at local, regional and global levels.
Keywords: Q54; Q57; 330; Meta-analysis; Coral Ecosystem; Valuation; Willingness to Pay; Biases